2018
DOI: 10.1007/s00432-018-2626-4
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage oligomeric matrix protein is a prognostic factor and biomarker of colon cancer and promotes cell proliferation by activating the Akt pathway

Abstract: COMP may be a novel prognostic indicator and biomarker and also a potential therapeutic target for colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 32 publications
3
59
0
Order By: Relevance
“…It has been suggested as an independent prognostic marker for breast cancer ( 41 ). Liu et al ( 42 ) established COMP-knockout cells to detect the effects of COMP on colon cancer cells and found that knockout of COMP could suppress cells proliferation, clonogenicity, and tumor growth, while increasing sensitivity to chemotherapy. These findings indicate that COMP may be also a potential therapeutic target for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested as an independent prognostic marker for breast cancer ( 41 ). Liu et al ( 42 ) established COMP-knockout cells to detect the effects of COMP on colon cancer cells and found that knockout of COMP could suppress cells proliferation, clonogenicity, and tumor growth, while increasing sensitivity to chemotherapy. These findings indicate that COMP may be also a potential therapeutic target for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al . 39 reported that COMP is the biomarker for colon cancer and could promote the cell proliferation through Akt pathway. Stracke et al .…”
Section: Discussionmentioning
confidence: 99%
“…COMP can reportedly prevent apoptosis by inducing the expression of apoptosis inhibitors 5 - 8 . COMP is also a prognostic factor and biomarker of colon cancer and promotes cell proliferation by activating the Akt pathway 9 , 10 . In addition, COMP initiates cancer stem cells by activating Jagged1-Notch3 signaling 11 .…”
Section: Introductionmentioning
confidence: 99%